Investigation of energy storage applications on nickel fluoride nanomaterials under shock wave flow environments - S, Arumugam; Kim, Ikhyun (Malaysian NANO-An International Journal, 2023)
In this research article, we have conducted the comparative studies on ambient and 200 shock loaded NiF2 sample using a table top pressure-driven shock tube (Reddy Tube) for supercapacitor application. The stability of structural, morphological and electrochemical properties of the shock loaded and unloaded were tested and analysed. The shock wave of 2.2 Mach number with transient pressure of 2.0 MPa with 864 K temperature was made to strike on two test samples (ambient and 200). The molecular and crystallite structure stabilities of the test samples were examined by XRD and FTIR. The surface morphology was investigated by FESEM and electrochemical measurements such as Cyclic Voltammetry (CV), Galvanostatic Charge-Discharge (GCD) techniques were performed to investigate the super capacitive behaviour of NiF2 sample for loaded and unloaded conditions. The obtained results revealed changes in crystallite size and particle size and it still maintains its phase stability of rutile NiF2 after 200 shocked conditions. Further, the electrochemical measurements exhibit higher capacitance of 1770.5 F/g for 200 shock loaded condition which is very high range when compared with ambient condition. Furthermore, it measured high energy density (88.52 Wh/kg) and power density (1499.8 W/kg) at 2 A/g current density which is very higher compared to others. Hence under high shocked conditions, the electrochemical properties were enhanced due to shock wave impacts on the NiF2 material.